Investigation of the thermomechanical performance of hybrid polymer composite using micro bamboo powder and graphite flakes. Issue 11 (26th October 2021) - Gouda, Krushna; Paul, Rajdeep; Bhowmik, Sumit; Das, Biplab
Abstract: The current research project is dedicated to tackling the issue of fiber alignment and composite material delamination. Alkali treatment is performed to enhance the bamboo filler reinforced composite's mechanical performance as well as interfacial bonding strength. The hybrid composite is developed with varied bamboo powder content from 2.5 to 12.5 wt% and graphite nanoplatelets (GN) are reinforced in the polymer matrix. The hybrid composite is manufactured with bamboo powder approximately 65 μm sized and GN for electrical and electronics packaging, heat sink, conductive paste, light back cover for thermal management, automobile parts, and packaging goods. The developed material is investigated experimentally through the tensile test, modulus of elasticity, storage modulus, thermal conductivity, corrosion and tribological analysis. Results revealed that 5 and 7.5 wt% bamboo filler with 1 wt% GN gives the best property among others. Abstract : The work mainly evaluated the mechanical performance of the bamboo filler reinforced polymer composite with graphite nano plates for different thermal conductive applications. The bamboo filler was varied at different wt.% whereas the wt.% of graphite nano plates kept constant. From the results it was found that the 7.5% wt. the hybrid composite shows the best performance.